Eucalyptus-based products range as an example of modern approaches to the creation of herbal drugs - Khvorost, O.; Oproshanska, T.; Skrebtsova, K.; Fedchenkova, Yu.; Rudnik, A. M.; Рудник, Анна Михайлівна (My University, 2025)
Introduction. Given the popularity of eucalyptus leaves and various forms of BAS extracted from this type of raw material, and the current focus of pharmacological action, it is relevant to investigate the Ukrainian pharmaceutical market of eucalyptus raw materials and products based on it. The purpose of the work is to investigate the Ukrainian market of eucalyptus-based products of pharmaceutical, food and cosmetic orientation. Methods: content analysis of information from the compendium, literary sources, pharmacy websites, trading platforms, etc. Results and discussion. The market contains raw materials (whole, cut, ground and leaf powder) from 23 manufacturers, of which the majority are state (up to 90%). Only 25% of manufacturers indicate the type of plant whose leaves they sell: E. viminalis (5 manufacturers) and E. globulus (1 manufacturer), the rest do not mention the species affiliation. In addition, there are collections, teas and herbal teas (a total of 12 items) which, except to eucalyptus leaves, contain medicinal plant raw materials (MPM), belonging to 21 families. On the pharmaceutical market of Ukraine, essential oil of eucalyptus is available from 21 manufacturers, most of which do not indicate the name of the raw material from which this oil is obtained. Only 6 manufacturers indicated that it is essential oil of Corymbia citriodora, E. radiata and E. globulus (2 manufacturers for each type of raw material). Most often, oil is offered for sale in a volume of 10 ml, but there are options of 5 ml, 30 ml (ounce), and even 50 ml and 100 ml (Aromatics, Ukraine). 54% of manufacturers are Ukrainian, from foreign ones – products from 6 countries are presented, of which manufacturers from Switzerland and France dominate (11.5% each), the Czech Republic and India (7.7% each). There is information about 2 aroma compositions. On the pharmaceutical market, there are medicines with eucalyptus leaf extracts, which are produced by manufacturers from 10 countries (Fig. 5). Two-thirds of the manufacturers are state (67.8%), German ones make up 10.8%, Pakistani ones – 7.5%. The rest are manufacturers from the USA (4.3%), India (3.2%), Turkey (2.2%) and Poland, Vietnam, Spain (1.1% each). The dominant type of forms with eucalyptus leaf extracts are soft (27%), of which more complex and combined balms and ointments. Liquid dosage forms are represented mainly by inhalation solutions (8 options), tinctures: simple (6) and complex (3). Granules (sachets) predominate among solid dosage forms. Cosmetics (9%) are represented by hydrosols, soap, foot serum, skin elixir, bath concentrate and perfume. Conclusions. The variety of products (pharmaceutical, food, cosmetic industries) based on raw materials, extracts from it and essential oil confirms its demand in healthcare, food and cosmetic industries. A certain drawback is the unclear segmentation of the market of pharmaceutical (medicines), food (herbal teas, teas) and cosmetic (hydrolates, extracts) direction, which creates difficulties in consumer orientation. However, the modern Ukrainian market of pharmaceutical products based on eucalyptus leaves and extracts from it presents a variety of dosage forms with different combinations of components, which may be the basis for creating an effective algorithm of approaches to the development of dosage forms of new types of APIs with the relevant direction of action.
Keywords: eucalyptus; leaves; collections; drugs